Joining of SiAlON to Nitrided Duplex Stainless Steel at Elevated Temperature - ABDELRAHMAN ALI GASIM, ALRASHEED (IRC, 2017)
Joining the SiALON to the steel utilizes the properties of the two materials which could open a new path for different applications. However, the increment in the residual stress in the joint layers between the SiAlON and the duplex stainless steel can cause failure in bonding. This report investigated and compared the physical and mechanical properties as well as the growth in the interface layer of the bonding at different hot pressing periods. The experiment included nitriding of the duplex stainless steel and after that followed by joining process using hot press. Besides that, analyzing methodology included optical microscope, hardness tester and scanning electron micro-scope. The study on growing of the interface layer proved that two hours joining was enough to grow the thickness of the interface and increase the hardness of the reaction layers more than the three hours of joining.